MGF360-9L Is a Major Virulence Factor Associated with the African Swine Fever Virus by Antagonizing the JAK/STAT Signaling Pathway - Zhang, Keshan; Yang, Bo; Shen, Chaochao; Zhang, Ting; Hao, Yu; Zhang, Dajun; Liu, Huanan; Shi, Xijuan; Li, Guoli; Yang, Jinke; Li, Dan; Zhu, Zixiang; et al. (mBio, 2022)
African swine fever—an acute, febrile, hemorrhagic, highly contacting, and highly lethal disease caused by African swine fever virus (ASFV)—jeopardizes the global pig industry. Understanding the mechanism ASFV employs to evade host defense during infection is essential for developing targeted drugs and vaccines against ASFV. African swine fever (ASF)—an aggressive infectious disease caused by the African swine fever virus (ASFV)—is significantly unfavorable for swine production. ASFV has a complex structure and encodes 150–167 proteins; however, the function of most of these proteins is unknown. This study identified ASFV MGF360-9L as a negative regulator of the interferon (IFN)-β signal. Further evidence showed that MGF360-9L interacts with signal transducer and activator of transcription (STAT) 1 and STAT2 and degrades STAT1 and STAT2 through apoptosis and ubiquitin–proteasome pathways, respectively. Subsequently, the activation of IFN-β signaling was inhibited. Naturally isolated or genetically manipulated live attenuated viruses are known to protect against the virulent parental ASFV strains. Therefore, through homologous recombination, we deleted MGF360-9L from the virulent ASFV CN/GS/2018 strain to construct a recombinant strain, ASFV-Δ360-9L. Compared with the parent ASFV CN/GS/2018 strain, the replication level of ASFV-Δ360-9L decreased in primary porcine alveolar macrophage cultures at 24 h postinfection, but the difference is unlikely to be biologically relevant. Notably, ASFV-Δ360-9L was partially attenuated in pigs. To our knowledge, this study is the first to uncover the function of MGF360-9L during ASFV infection. MGF360-9L inhibits IFN-β signaling through the targeted degradation of STAT1 and STAT2. Furthermore, MGF360-9L is a key virulence gene of ASFV. Our findings reveal a new mechanism by which ASFV inhibits host antiviral response; this might facilitate the development of live attenuated ASFV vaccines. IMPORTANCE African swine fever—an acute, febrile, hemorrhagic, highly contacting, and highly lethal disease caused by African swine fever virus (ASFV)—jeopardizes the global pig industry. Understanding the mechanism ASFV employs to evade host defense during infection is essential for developing targeted drugs and vaccines against ASFV. To our knowledge, this study identifies the mechanism of innate immunity against by MGF360-9L and the effect of MGF360-9L on ASFV pathogenicity. The results showed that MGF360-9L may help ASFV escape the host immunity by degrading STAT1 and STAT2 and thus inhibiting IFN-β signaling. MGF360-9L is also an important virulence factor of ASFV. The deletion of MGF360-9L reduces ASFV virulence in pigs. This study explored a new mechanism of ASFV against innate immunity and identified a new ASFV virulence factor; these findings may guide the development of live attenuated ASFV vaccines.